Determination of the Peak and Residual Shear Strengths of the Sandwich Material in Slopes. (30th April 2017) - Hu, Qijun; Cai, Qijie; He, Leping; Yang, Xiaoqiang; Ye, Tao; Shi, Rendan
Abstract : The mudded weak interlayer is a geotechnical sandwich material exhibiting strain softening behavior, which plays an important part in the slope stability. The present work primarily focuses on the shear strength of the mudded weak interlayer in rock slopes. To determine the peak and residual shear strengths of the mudded weak interlayers, the particle flow code (PFC) is used to simulate the failure behavior during the direct shear tests. Laboratory investigations including uniaxial compression test, SEM, and 3D deformation measurement are employed to calibrate the essential micro parameters of the mudded weak interlayer during the simulation process in PFC. The numerical model is built based on these parameters and both the peak and residual shear strengths can be predicted from the model. The prediction results show that the peak and residual internal friction angle are 19.36° and 14.61°, while the peak and residual cohesion are 22.33 kPa and 2.73 kPa, respectively. Moreover, to validate the obtained peak and residual strengths, the results are compared with literature data. The peak and residual shear strengths of the mudded weak interlayer can serve as an important benchmark to evaluate the stability of side slopes and provide guiding suggestions for their reinforcement.